Evaluation of irritation potential of surfactant mixtures - (:unkn) unknown (Blackwell Publishing Ltd., 1999)
Irritation potential of sodium laureth sulfate (SLES) alone, and in combination a lauryl glucoside (LG), polysorbate 20 (PS) and cocoamidopropyl betaine (CAPB) was tested in 13 human subjects. Four main and six sub-formulations were prepared and evaluated. Formulations were applied to the forearm as a 24 h close patch study. Irritation was scored by two different methods using an in vivo clinical protocol based on visual scoring and on the stratum corneum capacitance measurement. Irritation was found to be dose dependent. At 2 mg/patch level ten subjects did not show any skin reaction. At 20 mg/patch level eleven subjects showed a broad range of skin irritation. The highest irritation was observed with the formula that contained SLES, LG, and cocamide DEA together. Among the sub-formulations, cocamide DEA showed the highest irritation grade. A statistically significant correlation was observed between visual clinical and corneometer scores. It was concluded that the irritation potential of surfactants was related to the total surfactant concentration, application mode, and the thermodynamic activity of molecules in the solution as well as the chemical structure of the surfactant molecules.
Keywords: Betaine; Capacitance measurement; Erythema; Lauryl glucoside; Skin irritation; Sodium laureth sulfate; Surfactants